Till summer do us part - Quinn, Meghan (Bloom Books, 2025)
"Scottie Price just started a new job, and it's a real sausage fest. She's the only woman on a team filled with Brads and Chads. Expecting a bachelor pad atmosphere, she is quickly corrected when she finds out everyone is happily married. In an effort to impress her boss, Scottie mentions her nonexistent husband in a company meeting. But eagle-eyed Chad points out her lack of wedding ring. Panicked, Scottie creates a story about her unhappy marriage. Unfortunately for Scottie, her boss has a solution--a one-on-one session with the best marriage counselor in the Northeast, who happens to be her boss's husband. With no way out of her lie, Scottie agrees to see him. Frantic, she calls in help from her best friend who sets her up with his brother, an improv-obsessed millionaire. Enter Wilder Wells. More than happy to take on the job, he teaches Scottie the main rule of improv: always say yes. But the rule backfires during the session when Wilder signs them up for an eight-day summer marriage camp with all of Scottie's co-workers where she'll have to share a cabin with her way-too-handsome fake husband."--Back cover.